1987
DOI: 10.1002/macp.1987.021880315
|View full text |Cite
|
Sign up to set email alerts
|

Single crystal structure of a polymerization active Nd‐Al bimetallic complex

Abstract: A polynuclear Nd-AI bimetallic complex in single crystalline form, which is active for diene polymerization, was isolated and its detailed structure was determine9 by X-ray diffraction technique. The results indicate that the crystal is triclinic, space group P1; the lattice parameters are: a = 15,195 (6), b = 15,263 (9, c = 13,749 (4) A; a = 90,Ol (2), / 3 = 95,12 (3), y = 82,65 (3)"; V = 3 149,5 A'; Z = 1 . The coordination number of the Nd atom is seven and the configuration is monocap-prism. Nd atoms can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
1

Year Published

1995
1995
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 7 publications
1
18
0
1
Order By: Relevance
“…In 1987, Shan demonstrated existence of two kinds of active species in the ternary system Nd(O i Pr) 3 / AlEt 3 /AlEt 2 Cl by analyzing the single crystal of active species of X-ray diffraction pattern (Fig. 2) [25]. Boisson et al suggested that the A type active species in Fig.…”
Section: Comparison Of Catalytic Activity Of Three Catalytic Systemsmentioning
confidence: 98%
“…In 1987, Shan demonstrated existence of two kinds of active species in the ternary system Nd(O i Pr) 3 / AlEt 3 /AlEt 2 Cl by analyzing the single crystal of active species of X-ray diffraction pattern (Fig. 2) [25]. Boisson et al suggested that the A type active species in Fig.…”
Section: Comparison Of Catalytic Activity Of Three Catalytic Systemsmentioning
confidence: 98%
“…Moreover, cluster molecules can act as model systems for addressing delicate questions in catalysis science by giving insight into unique coordination modes and reactivities 6. 7 In organometallic cluster chemistry, trailblazing structural reports such as those of the inorganic fullerene‐like molecule [{Cp*Fe(η 5 :η 1 :η 1 :η 1 :η 1 :η 1 ‐P 5 )} 12 {CuCl} 10 {Cu 2 Cl 3 } 5 {Cu(CH 3 CN) 2 } 5 ]8 and low‐valent aluminum complexes [Al 50 Cp* 12 ] 9a or [SiAl 14 Cp* 6 ] 9b bear witness to the uniqueness of the ubiquitous cyclopentadienyl ancillary ligand environment in d‐transition‐metal and main‐group‐metal chemistry (Cp*=C 5 Me 5 ) 10. Because of its steric bulk, rigidity, and thermal and chemical stability, the Cp ligand and its substituted variants are also ideal for cluster design/stabilization involving the large oxophilic rare‐earth metal ions, which participate predominantly in ionic bonding 11.…”
Section: Structurally Characterized Half‐sandwich Organolanthanide CLmentioning
confidence: 99%
“…Solche Clusterverbindungen können auch als Modellverbindungen zur Erörterung bisher ungeklärter Fragestellungen innerhalb der Katalysatorforschung fungieren, indem sie Einblick in einzigartige Koordinationsmuster und Reaktivitäten geben 6. 7 In der Chemie der Organometallcluster bezeugen bahnbrechende Strukturbeschreibungen wie die der fullerenartigen anorganischen Verbindung [{Cp*Fe(η 5 :η 1 :η 1 :η 1 :η 1 :η 1 ‐P 5 )} 12 {CuCl} 10 {Cu 2 Cl 3 } 5 {Cu(CH 3 CN) 2 } 5 ]8 und der niedervalenten Aluminiumkomplexe [Al 50 Cp* 12 ]9a oder [SiAl 14 Cp* 6 ]9b die Einzigartigkeit des häufig eingesetzten Cyclopentadienyl‐Hilfsliganden in der d‐Übergangsmetall‐ und Hauptgruppenmetallchemie (Cp*=C 5 Me 5 ) 10. Wegen ihrer sterischen Abschirmung, Starrheit und sowohl thermischen als auch chemischen Stabilität sind der Cp‐Ligand und seine substituierten Varianten auch prädestiniert für das Design und die Stabilisierung von Clustern unter Einbeziehung großer, oxophiler Seltenerdmetallionen, deren Bindungen einen hohen ionischen Anteil aufweisen 11.…”
Section: Strukturell Charakterisierte Halbsandwich‐organolanthanoid‐cunclassified